The Correlation of Cyp2e1 Genetic Polymorphism on Alcohol Drinking Habits in Papuan Ethnicity - Mardhatillah Marsa; Yudha Nurhantari; Suhartini Suhartini; Tri Ratnaningsih (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Alcohol abuse is associated with genetic factors and is influenced by certain races and ethnicities. CYP2E1, which works on the endoplasmic reticulum, produces an enzyme that plays a significant role in alcohol metabolism. In relation to it, this study aims to identify the polymorphisms of CYP2E1*5B and CYP2E1*6 genes in alcohol drinkers of Papuan Ethnics. A total of 39 Papuans were analyzed for alcohol drinking habits. Alcohol drinkers were found to be 29 people (74.4%), and 10 people (25.6%) were non-drinkers. The drinkers mainly were late teenagers (89,7%) and males (69,2%). The CYP2E1*5B genotypes were c1/c1 as 94.9% and c1/c2 as 5.1%. Meanwhile, the CYP2E1*6 T/T genotypes were 56.4%, and T/A genotypes were 43.6%. The odd ratio for CYP2E1*5B were 18,5 and 7,7 for CYP2E1*6. p0,05 for CYP2E1*5B and CYP2E1*6 gene polymorphisms for alcohol drinking behavior in the form of frequency, duration, type, and volume of alcohol consumed. Furthermore, c1/c1 and c1/c2 genotype polymorphisms were in CYP2E1*5B; T/T and T/A genotypes were in CYP2E1*6 of Papuan ethnic at Yogyakarta. In conclusion, genotype c1/c1 had 18,5 times of the possibility of being alcoholic drinkers, and genotype T/T had 7,7 times of the possibility of being alcoholic drinkers in Papuan ethnic. It indicated that the type of genotype statistically did not significantly affect alcohol drinking behavior on the subject.